Pengaruh Game Edukasi “Secil” terhadap Keterampilan Membaca Permulaan Anak Usia Dini di Taman Kanak-kanak - Rahmadani, Putri; Muryanti, Elise (AS-SABIQUN, 2023)
Skills of early reading are very urgent to be stimulated in early ages. The purpose of research is to reveal the "Secil" Educational Game (Small Learning Series) effect on Early Childhood Early Reading Skills in Kindergarten Fadhilah Amal 3 Padang. This research used an approach in quantitative in the shape of a Quasi Experiment. The technique for data collection was in the shape of action test (pre-test and post-test). The technique for sampling was Purposive Sampling, we know as class B1 and class B2, all of which consisted of 10 children. The technique for data analysis was conducted by using statistics with the support of the SPSS 21.0 application for windows. The result given that, there were an increase score of the control class which is at 254 for pre-test and post-test at 315. Meanwhile, the control class average is for pre-test is at 25.4 and post-test at 31.5. Thus, there is an improve in children's early reading skills by using the "Secil" educational game in the experimental group with pre-test score is at about 265 and a post-test at about 443. Overall, the average score for the pre-test is 26.5 and the post-test is 44.3. The result given that, there is an improve of early reading skills in the class for experimental compare to control class. Therefore, the android-based "small" educational game is very effective to increase early children early reading skills.